Absenteeism and Labour Turnover in Selected Ontario Industries - Robertson, Gordon (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1979)
The primary objective of this survey is therefore to collect enough data to in order that comparisons of absenteeism and labour turnover can be made within various regions and industries in Ontario. The study also provides general information on the extent, nature and relative importance of various human problems.